Novel and potential future therapeutic options in systemic autoimmune diseases - Balogh, Lili; Oláh, Katalin; Sánta, Soma; Majerhoffer, Nóra; Németh, Tamás (Frontiers in Immunology, 2024)
Autoimmune inflammation is caused by the loss of tolerance to specific self-antigens and can result in organ-specific or systemic disorders. Systemic autoimmune diseases affect a significant portion of the population with an increasing rate of incidence, which means that is essential to have effective therapies to control these chronic disorders. Unfortunately, several patients with systemic autoimmune diseases do not respond at all or just partially respond to available conventional synthetic disease-modifying antirheumatic drugs and targeted therapies. However, during the past few years, some new medications have been approved and can be used in real-life clinical settings. Meanwhile, several new candidates appeared and can offer promising novel treatment options in the future. Here, we summarize the newly available medications and the most encouraging drug candidates in the treatment of systemic lupus erythematosus, rheumatoid arthritis, Sjögren’s disease, systemic sclerosis, systemic vasculitis, and autoimmune myositis.